2021
DOI: 10.1039/d0nj04712k
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sensitive and selective determination of a phenolic food additive using protein capped gold nanoclusters: a dual in-line fluorometric and colorimetric sensing probe

Abstract: The application of red luminescence BSA-AuNCs towards the selective determination of food additive tert-butylhydroquinone (TBHQ) was demonstrated by both fluorometric and colorimetric methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Recently, the colorimetric detection of various other food additives such as azodicarbonamide (ADA) and sodium benzoate was also reported using nanomaterials. 121,122 For example, a MnO 2 nanosheet-3,3′,5,5′-tetramethylbenzidine-glutathione (MnO 2 -TMB-GSH) based oxidative detection system was devel-oped for the detection of ADA in flour samples (Fig. 2).…”
Section: Colorimetric Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the colorimetric detection of various other food additives such as azodicarbonamide (ADA) and sodium benzoate was also reported using nanomaterials. 121,122 For example, a MnO 2 nanosheet-3,3′,5,5′-tetramethylbenzidine-glutathione (MnO 2 -TMB-GSH) based oxidative detection system was devel-oped for the detection of ADA in flour samples (Fig. 2).…”
Section: Colorimetric Sensorsmentioning
confidence: 99%
“…In the presence of interferents, the results demonstrated that the suggested approach was highly selective for TBHQ (ranging from 2.5 to 50 mM) with a LOD of 72 nM. 122 In another study, organic NPs based on a tetraphenyl imidazole compound (TIBM) were employed for the development of a "TURN-ON" sensor to detect sulfite (a food preservative) within 15 seconds. 124 The analyte was detected via aggregation-induced emission enhancement (AIEE) in the presence of sulfite.…”
Section: Fluorescent Sensorsmentioning
confidence: 99%
“…If Au NCs were prepared using bovine serum albumin (BSA) as protective ligands, 33 the removal of BSA ligands leads to changes in the properties of BSA−Au NCs. Trypsin is an endopeptidase that could hydrolyze arginine and lysine peptide chains in BSA molecules, 34 so trypsin can hydrolyze BSA ligands on the surface of BSA−Au NCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…So far, great advances have been got in the quantitative research and analysis of TBHQ. Common analysis methods for the determination of TBHQ include high-performance liquid chromatography, gas chromatography–mass spectrometry, electrochemical methods, fluorimetric detection, and capillary electrophoresis. Among the above methods, the fluorescence analysis method is considered to be the most prospective technology due to its high sensitivity and selectivity . Moreover, fluorescence detection is simple, time-saving, low cost, and convenient; thus, fluorescent sensors could be potential candidates for monitoring TBHQ .…”
Section: Introductionmentioning
confidence: 99%